Implementation of E-Voting According to the Perspective of Constitutional Law - Suroto, Suroto (STMIK Dharma Wacana, 2022)
Seeing the implementation of the 2019 General Election, where a lot of sad news became public news, the 2019 Election was given the wrong label by the public. In addition, with the development of information technology (ICT), the results of a general election are also required to be known immediately. E-Voting promises that information on election results can be obtained quickly and in real-time through ICT in sending and counting votes and can minimize bad election results that occurred in 2019, as in the case of vote counting recapitulation. Therefore, this study aims to discuss the application of E-Voting according to the perspective of constitutional law to obtain legal certainty. This research is normative legal research. The results show that implementing elections with E-Voting is better because it will minimize the use of human resources and costs, facilitate vote recapitulation, already has legality through the EIT Law, reduces implementation, and prevents fraud. From the perspective of constitutional law, general elections with e-voting do not violate the principles of elections and the constitution; where this has been tested through the Constitutional Court with the issuance of the Constitutional Court Decision Number 147/PUU-VII/2009, which was further legitimized into Law Number 10 of 2016 concerning Regional head elections which state that voting for elections can be done by voting through electronic voting equipment.